Global trends in polycystic ovary syndrome research: A 10-year bibliometric analysis - Shi, Na; Ma, Hong-bo (Frontiers in Endocrinology, 2023)
Background: Polycystic ovary syndrome (PCOS) is one of the most common reproductive metabolic disorders in women, significantly affecting the biological functionalities of ovaries. This disease has garnered enormous interest from researchers. However, there is a lack of a comprehensive research concerning assessing the current status and future trends in PCOS field. This study uses bibliometric tools to comprehensively analyze the PCOS-related research progress based on the literature in the past decade. Methods: The reported PCOS literature in the past decade is downloaded from the Web of Science database. The bibliometric software is applied to analyze the co-authorship, co-citation, and co-occurrence status. Results: A total of 9293 publications imported into bibliometric tools for analysis show a sharp increase in the annual citations. The USA is dominant in terms of contribution in the field of PCOS, while China is making a significant contribution to the advancement of this field. The League of European Research Universities (LERU) is the most prolific institution with the highest H-index value. The contribution of the Robinson Research Institute from the University of Adelaide must be acknowledged. Legro RS and Teede HJ are the most active and influential authors in recent times, while Azziz R is the most contributed pioneer in this field. The Journal of Clinical Endocrinology & Metabolism is the most active journal with the highest number of publications and citations. The pathogenesis of PCOS had been a long-term forefront of research. In recent years, the health management in PCOS prevention and long-term complications was attracting more and more attention. The keywords like “gut microbiota”, “microRNAs”, “apoptosis”, “Myo-inositol”, “TNF-alpha”, “androgen receptor”, and “Vitamin D-deficient” are considered the latest research topics. Conclusion: The study comprehensively analyzes the current status and global trends in the PCOS field, providing a significant reference for researchers to explore this field effectively.